Faktor Kunci Adopsi Fintech dalam Moda Pembayaran Biaya Pendidikan (Studi pada Mahasiswa Politeknik Harapan Bersama) - Mohammad Alfian; Arifany Ferida; Arvin Nova Aditya Pratama (Owner : Riset dan Jurnal Akuntansi, 2023)
The industrial revolution 4.0 has driven changes in various sectors, including economics. The Covid 19 pandemic has also driven change by way of payment. The use of Fintech by students is one form of that change that occurs in the method of transactions that were previously carried out directly to indirectly. This study examines the determinants of students paying tuition fees using fintech. This study uses PLS analysis with the SmartPLS 3 test tool. The amount of data processed in this study was 171, which method was used in selecting the sample, namely random sampling. Based on the results of statistical tests conducted, it was found that the method of selecting fintech by students in paying tuition fees is influenced by trust, perceived benefits and user privacy and perceived risk of failing to influence it. Furthermore, the trust of students to use fintech in the study of baiaa payments is influenced by users perceptions, risks and privacy.